2017
DOI: 10.1002/app.46112
|View full text |Cite
|
Sign up to set email alerts
|

A novel thermosensitive triblock copolymer from 100% renewably sourced poly(trimethylene ether) glycol

Abstract: Bio-based amphiphilic triblock copolymers with 100% renewably sourced poly(trimethylene ether) glycol (PO3G) as the hydrophobic blocks and statistical copolymer of 2-(2-methoxyethoxy)ethyl methacrylate (MEO 2 MA) and oligo(ethylene glycol)methacrylate (OEGMA) [P(MEO 2 MA-stat-OEGMA)] as the hydrophilic blocks are synthesized and characterized. It is found that the molar ratio of MEO 2 MA/OEGMA among the resulting copolymers is approximately 70/30. The degree of polymerization (DP) of P(MEO 2 MA-stat-OEGMA) blo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 46 publications
0
7
0
Order By: Relevance
“…In this study, the PO3GCA copolymer was synthesized using a direct synthesis method [ 12 , 18 , 19 , 20 , 21 , 22 ]. Specifically, PO3G (300 g) and CA (21 g) were added to a 500 mL three-necked flask in a 1.3:1 molar ratio, with 0.5% (1.6 g) molybdenum trioxide used as the catalyst.…”
Section: Methodsmentioning
confidence: 99%
“…In this study, the PO3GCA copolymer was synthesized using a direct synthesis method [ 12 , 18 , 19 , 20 , 21 , 22 ]. Specifically, PO3G (300 g) and CA (21 g) were added to a 500 mL three-necked flask in a 1.3:1 molar ratio, with 0.5% (1.6 g) molybdenum trioxide used as the catalyst.…”
Section: Methodsmentioning
confidence: 99%
“…Poly(1,3-propanediol) (PO3G) is a 100% bioderived renewable polyether polyol developed by DuPont [26,27], which has repeating units similar to PEG and PPG. Therefore, PO3G may also have a plasticizing effect on PLLA, but no studies have been reported.…”
Section: Introductionmentioning
confidence: 99%
“…Bio‐based 1,3‐propanediol (1,3‐PDO) is corn‐derived raw materials, and is used to acquire 100% renewably sourced poly(trimethylene ether) glycol (PO3G) through polycondensation 9 . The renewable PO3G has been used as key ingredients in preparing reactive hot melt adhesive, 7 micelles, 10 and elastomers 11 . In our recent work, 12 bio‐based WPU based on PO3G (WPU‐PO3G) was prepared to reveal superior flexibility, abrasive‐ and hydrolysis‐resistance in comparison with petroleum poly(tetramethylene ether) glycol‐based WPU.…”
Section: Introductionmentioning
confidence: 99%